Short Messaging System (SMS) Reminder For Car Alarm Alert System - Iylia Shaleen , Ismail (UTeM, 2010)
Year by year, stolen car cases is increasing rapidly here in Malaysia. Statistics released by the police revealed that 5,920 Proton cars were stolen between January and October last year. As a car’s owner, a security system is needed to protect our car from dangers. There is no way to totally eliminate the car theft, but there are still ways to prevent cars from being stolen and being broke. Hence, A SMS Reminder for Car Alert Alarm System is created as an approach to protect our car. This system is a security system that is designed to protect and alert the user on certain happening that need prompt attention to the car. When any sensor of car alarm system activates, this module will forms SMS to inform the car’s owner. This project is design by using a transmitter, which transmit signals to another device that is the receiver that link with control system which defined as PIC microcontroller.The alarm will arm and it will sample its voltage then transmits it to PIC microcontroller. The Micro C Compiler programming can be used to monitor and transmit controlling signals to the modem by connecting a serial communication port RS232 between GSM modem and the hardware. AT command is used to control the function of the modem.